Inflanty Polskie Bolesława Limanowskiego – wspomnienia i relacje - Samborska-Kukuć, Dorota Karolina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
Polish Livonia was the little homeland of Boleslaw Limanowski, a socialist and a popular political activist. The author reminisces about it in his Memoirs and in his correspondence reviving the past – both private and the history of the region (his work about Emilia Plater). Limanowski’s statements, because of his highly detailed observations, are the source of the history of the province and character of its customs. They also reveal a private side of the evolution of the author’s views. His accurate remarks connected with the peculiarities of the identities of Poles living in Livonia, especially their relationships with Russians, enabled the reader to think about the uniqueness of the author’s thoughts and his sagacity.